Five dice, all threes [compact disc] (Dead Oceans, 2024)
A record of uncommon intensity and tenderness, communal exorcism, and personal excavation. These are, of course, qualities that fans have come to expect from Bright Eyes, nearly three decades into their career. The tight-knit band of Conor Oberst, Mike Mogis, and Nate Walcott tends to operate in distinct sweeping movements, each unique in sound and story but unified by a sense of ambition and ever-growing emotional stakes. Even with this rich history behind them, these new songs exude a visceral thrill like nothing they have attempted before. Oberst has always sung in a voice that conveys a sense of life-or-death gravity. On the self-produced album, Bright Eyes embrace the elusive quality that has made them so enduring and influential across generations and genres. In Oberst's songwriting lies a promise that our loneliest thoughts and feelings can take on grander shapes when passed between friends, blasted through speakers, or shouted among crowds.